Financialisation and stagnation: A macroeconomic regime perspective - Eckhard Hein (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2020)
In this contribution we link the recently re-discovered tendencies towards stagnation with the features of financialisation, which have started to dominate developed capitalist economies in the early 1980s. We review the main macroeconomic channels of transmission of financialisation-namely, the effects on distribution, investment in the capital stock, consumption and on the current and capital accounts. We distinguish three regimes, the debt-led private demand boom, the export-led mercantilist and the domestic demand-led regime and apply this to six countries, Germany, France, Spain, Sweden, the UK and the USA, as well as to the Eurozone, both for the period before (1999-2008) and after (2009-2018) the financial and economic crisis. We show that the dominance of the debt-led private demand boom regime, on the one hand, and the export-led mercantilist regime, on the other hand, has contributed to global current account imbalances before the financial and economic crisis 2007-9, which has demonstrated that these two regimes were unsustainable. For the period after the crisis we find a shift towards export-led mercantilist regimes and a move towards domestic demand-led regimes stabilized by government debt with global current account imbalances persisting. Finally, we elaborate on the challenges of these developments, a highly fragile global constellation with severe problems of aggregate demand generation and a tendency towards stagnation caused by high inequality and weak capital stock growth.
Keywords: E02; E60; E61; F62; G38; 330; Wirtschaftskrise; Finanzkrise; Makroökonomik; Deutschland; Frankreich; Spanien; Schweden; Großbritannien; USA